Pelabelan L(2,1) pada Graf Sierpinski S(n,k) - Sagala, Yuri; Susiana, Susiana (Universitas Negeri Medan, 2018)
Labeling L (2; 1) on a graph G is the function f of the set of vertices V (G) to the set of all non-negative numbers so that │f (u) - f (w) │ ≥ 2 if d (u; w) = 1 and │f (u) - f (w)│ ≥ 1 if d (u; w) = 2. The labeling number L (2; 1) of a graph G is the smallest k number so G has labeling L (2; 1) with max f (v): v Є V (G) g = k. The Sierpinski Graph is a form of expansion graph specifically from a complete graph. This study shows labeling on Sierpinski graph using Chang-Kuo algorithm and obtained the values L (2; 1) S (n; 2) = 4 and the value of L (2; 1) S (n; 3) = 6 for n ≥ 2, with L (2; 1) G is the smallest maximum number labeling L (2; 1) from a graph G. [LABELING L(2,1) IN SIERPINSKI S(N,K)](J. Sains Indon., 42(1): 22-24, 2018)Keywords:Graph Labeling L(2,1), Sierpinski Graph